Accounting for Revenue from Cryptocurrency and Other Digital Asset Transactions at IT Enterprises - SEMENOVA, S. M.; SHPYRKO, O. M.; AFANASIEVA, I. I. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article is devoted to the theoretical and practical justification of a unified approach to the recognition of income from transactions with cryptocurrency and other digital assets at IT enterprises, which is based on the analysis of existing accounting methods and the requirements of International Financial Reporting Standards, and also contains recommendations for increasing the transparency and comparability of financial reporting in the IT sector. Enterprises operating in the IT sector are characterized by a high intensity of microtransactions and the widespread use of various tokens, which is accompanied by significant volatility, tax and legal uncertainties. Despite the existing interpretations of the norms of international standards, there is no unanimity regarding the criteria for classifying cryptocurrency and other digital assets as inventories, intangible assets and financial instruments, as well as the choice of valuation methods in conditions of irregular liquidity and fragmented disclosure in the notes. This creates an urgent need to develop unified recommendations for accounting for income from transactions with cryptocurrency and other digital assets, which will ensure the consistency of the application of international standards, increase transparency of reporting and reduce tax risks. It was found that the lack of a special standard and clear regulatory requirements causes significant discrepancies in the classification, valuation and disclosure of information on transactions with digital assets. The practice of IT companies was analyzed and it was demonstrated that the implementation of internal accounting policies consistent with the requirements of international standards, combined with the use of leading analytical platforms and independent custodial services, allows to increase the reliability of data and minimize the risks of fraud. Given the high volatility of the market, it is recommended to use adaptive valuation methods (weighted average prices, revaluation corridors) and scenario analysis, as well as to reflect cryptocurrency and other digital assets in the reporting separately with detailed disclosure in the notes. The role of crypto-accounting, which is developing as a modern direction of accounting and combines methodological, organizational and technological solutions for reflecting transactions with cryptocurrencies and digital assets in accounting and reporting in accordance with the requirements of standards, features of the digital environment and legal restrictions, is emphasized. Based on the research, a unified methodology for recognizing, evaluating and reflecting transactions with cryptocurrency and other digital assets has been formed, which ensures strict compliance with the requirements of International Financial Reporting Standards, increases transparency and completeness of information disclosure, and also significantly reduces regulatory and financial risks for IT enterprises.